Polyphenols and Rosmarinic acid Contents, Antioxidant and Anti- Inflammatory Activities of Different Solvent Fractions from Nga- Mon (Perilla frutescens) Leaf - Kanokkarn Phromnoi; Maitree Suttajit; Chalermpong Saenjum (Journal of Pharmacy and Nutrition Sciences, 2019)
Perilla is a rich source of polyphenols, which exhibits antioxidant, anti-inflammatory activities, and a variety of biological effects. The effect of differential solvents on the polyphenols, flavonoids, rosmarinic acid (RA), antiinflammatory and antioxidant activities of perilla leaf require investigation. In this study, perilla leaf was extracted with 70% ethanol and sequentially fractionated according to the solvent’s polarity with hexane, dichloromethane, ethyl acetate, and water. Samples were subjected to the bioactive compound measurements. The antioxidant and antiinflammation nature of perilla was analyzed based on the scavenging effects on DPPH•, ABTS•+, O2•- and nitric oxide (NO), as well as FRAP assay, and determination of the inhibition effects on NO, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) production in the cell-based study. The results indicate that among all different solvents used for sequential fractionation, ethyl acetate (EtOAc) was most effective in the separation of anti-oxidative and antiinflammatory compounds in the perilla leaf extract. These properties can partly be due to the presence of polyphenols, flavonoids, and also RA. It can be demonstrated here that, the perilla leaf EtOAc fraction could be used as a natural active pharmaceutical ingredient for dietary supplements and nutraceuticals.